Thematisation of Recognition in the Anthropological Reflections of Pierre Bourdieu - Boreiko, Y. H.; Fedotova, T. V. (Anthropological Measurements of Philosophical Research, 2025)
Purpose. The purpose of the study is to elucidate the essence of the concept of recognition in the context of the philosophical and anthropological views of the French sociologist Pierre Bourdieu. The main objectives include analyzing the scholar’s critique of philosophy as "scholastic" theorizing, reconstructing his philosophical and anthropological ideas, and uncovering the existential significance of the human striving for recognition. Theoretical basis. The research builds on Bourdieu’s interpretation of recognition as a fundamental existential goal through which individuals seek to justify the meaning and purpose of their existence. In his concept of recognition, Bourdieu identifies the desire for authority, status, and prestige – components of symbolic capital – as the primary driver of human behavior. This symbolic capital, however, can only be accumulated within society. Simultaneously, recognition becomes a source of competition and rivalry for possession of symbolic capital, driving societal development. At the core of Bourdieu’s philosophical and anthropological ideas lies an attempt to frame the subject of study within objective structures, thereby aligning subjective human experience with the impact of external social structures. Originality. Taking into account Bourdieu’s critique of the "systemic" flaws of philosophy, which is dominated by a "scholastic" mindset, this study reconstructs his philosophical and anthropological ideas rooted in the empirical trajectory of his research, which is primarily grounded in sociological analysis. The concept of recognition is presented as the societal counterpart to the theological notion of justification, serving as a foundation for understanding the meaning of human life. The agonistic nature of the concept of symbolic capital highlights recognition as a constitutive dimension of human existence in society. Conclusions. Sociological analysis, as a prerequisite for Bourdieu’s philosophical and anthropological reflections, does not imply a rejection of philosophical methodology. Instead, it underscores a belief that sociological tools are better suited for constructing of a universal human concept. Since Bourdieu’s ideas were shaped by studying specific sociological scenarios, which in turn formed his theoretical framework, his concepts should be viewed as both the prerequisites for and the outcomes of this methodology. From this perspective, Bourdieu’s understanding of recognition in the social field emerges as the result of human interaction with social structures and other individuals who impose demands and set tasks, facilitating the acquisition of social status – that is, the accumulation of symbolic capital.